EFEKTIVITAS PEMEKARAN NAGARI TANDIKEK UTARA KECAMATAN PATAMUAN KABUPATEN PADANG PARIAMAN - Basri, Gustia Linanda; Rusli, Zaili (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Expansion is one of the effects phenomenon regional autonomy. Movementthe expansion of government admnistration area from top up level arrive down tolowest level namely the Villages in Minangkabau Culture at Province West Sumatra.The purpose are improving public service and the development of accelerated . In201o, expansion of north Tandikek the village with the status of increased ParamanTalang disk and Lubuk Laweh disk in accorded with together of agreement. Theproblems of this research are how the effectiveness of north Tandikek the VillagesPatamuan District Padang Pariaman Regency and the factors that’s influence theeffectiveness.The research used effectiveness theory by Duncan. This theory consists ofthree variebel that’s Achieved the goal, Integration and adaptation. The method ofthe research was qualitative using snowball sampling technique in selecting theinforman. Informan in this research Head Parts governmentof villages, headPatamuan District, Head North Tandikek Village and Community leaders northTandikek Villages.The result of this research it was found that effectivenesse expansion of northTandikek the village based on on the research conclusion enough effective. Based oneffectiveness theory by Duncan, evidently with many changes and significantprogress in alls area social,economy, education and culture in North TandikekVillage. The factors that influence are human resources, cooperation, facilities andinfrastructure and community participations. There was expansion get northTandikek the villages become the villages of progress and superior through trainingfoundationand the progressof human resources .Key word : Effectiveness, Expansion, village and North Tandikek the Villages.